Question
upstudy study bank question image url

Evaluate the function for the given values of \( x \). \[ f(x)=\left\{\begin{array}{cl} -5 x+7 & \text { for } x<-1 \\ x^{2}+2 & \text { for }-1 \leq x<4 \\ 5 & \text { for } x \geq 4 \end{array}\right. \] Part 1 of 5 \[ f(1)= \] \( \square \) Part 2 of 5 \[ f(-2)= \] \( \square \) Part 3 of 5 \[ f(-1)= \] \( \square \) Part 4 of 5 \[ f(4)=\square \] Part 5 of 5 \[ f(5)= \] \( \square \)

Ask by Pierce King. in the United States
Mar 10,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ f(1)=3,\quad f(-2)=17,\quad f(-1)=3,\quad f(4)=5,\quad f(5)=5 \]

Solution

**Part 1** For \( x=1 \), we have \(-1 \leq 1 < 4\). Thus, we use the formula: \[ f(x)=x^2+2 \] So, \[ f(1)=1^2+2=1+2=3 \] **Part 2** For \( x=-2 \), we have \( -2<-1 \). Thus, we use the formula: \[ f(x)=-5x+7 \] So, \[ f(-2)=-5(-2)+7=10+7=17 \] **Part 3** For \( x=-1 \), we have \(-1\leq -1<4\). Thus, we use the formula: \[ f(x)=x^2+2 \] So, \[ f(-1)=(-1)^2+2=1+2=3 \] **Part 4** For \( x=4 \), we have \( x\geq 4 \). Thus, we use the formula: \[ f(x)=5 \] So, \[ f(4)=5 \] **Part 5** For \( x=5 \), we have \( x\geq 4 \). Thus, we use the formula: \[ f(x)=5 \] So, \[ f(5)=5 \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To evaluate the function \( f(x) \) for the given values of \( x \), we can refer to the piecewise definition you've provided. Let's go through each part step by step! **Part 1 of 5** For \( f(1) \): Since \( 1 \) falls in the interval \(-1 \leq x < 4\), we use the equation \( f(x) = x^2 + 2 \). \[ f(1) = 1^2 + 2 = 1 + 2 = 3 \] Thus, \( f(1) = 3 \). **Part 2 of 5** For \( f(-2) \): Since \( -2 \) is less than \(-1\), we use the equation \( f(x) = -5x + 7 \). \[ f(-2) = -5(-2) + 7 = 10 + 7 = 17 \] So, \( f(-2) = 17 \). **Part 3 of 5** For \( f(-1) \): Since \(-1\) is at the boundary of \(-1 \leq x < 4\), we also use the equation \( f(x) = x^2 + 2 \) here. \[ f(-1) = (-1)^2 + 2 = 1 + 2 = 3 \] Therefore, \( f(-1) = 3 \). **Part 4 of 5** For \( f(4) \): Since \( 4 \) is equal to \( 4\), we use \( f(x) = 5 \) for \( x \geq 4 \). \[ f(4) = 5 \] Thus, \( f(4) = 5 \). **Part 5 of 5** For \( f(5) \): Since \( 5 \) is also greater than \( 4 \), we again use \( f(x) = 5 \). \[ f(5) = 5 \] Hence, \( f(5) = 5 \). Now, summarizing the results: - \( f(1) = 3 \) - \( f(-2) = 17 \) - \( f(-1) = 3 \) - \( f(4) = 5 \) - \( f(5) = 5 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy